1948
DOI: 10.1128/jb.55.1.127-135.1948
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Certain Biological Characteristics of Malleomyces mallei and Malleomyces pseudomallei

Abstract: As a natural infection, glanders occurs only in horses, mules, and donkeys. Other animals occasionally become infected from contact with infected solipeds. The most susceptible of these occasionally infected species are ferrets, moles, field mice, cats, and dogs. Sheep, goats, hogs, rabbits, white, mice, and house mice are reported to be less susceptible, and cattle are iune (Hutyra and Marek, 1926). The guinea pig is considered to be the most susceptible laboratory animal. The virulence of various strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 2 publications
1
57
0
Order By: Relevance
“…Isolates were injected intraperitoneally into hamsters, and lethality was determined by observation for 2 days ( Table 3). The 95% confidence intervals were determined to be 1.340-3.610.DD503 was previously reported to have a 48 h log LD 50 value of less than 1 [24], and we further estimated the log LD 50 to be 0.6021 (Table 3), which is consistent with the published log LD 50 of B. pseudomallei in hamsters of 0.7782 [25]. Both the DsctU Bp1 and DsctU Bp2 mutants had LD 50 values similar to the parental strain; however, the DsctU Bp3 mutant was significantly attenuated with a log LD 50 of 3.3802 cfu.…”
Section: Ttss3 Is a Virulence Determinant In Hamsterssupporting
confidence: 85%
“…Isolates were injected intraperitoneally into hamsters, and lethality was determined by observation for 2 days ( Table 3). The 95% confidence intervals were determined to be 1.340-3.610.DD503 was previously reported to have a 48 h log LD 50 value of less than 1 [24], and we further estimated the log LD 50 to be 0.6021 (Table 3), which is consistent with the published log LD 50 of B. pseudomallei in hamsters of 0.7782 [25]. Both the DsctU Bp1 and DsctU Bp2 mutants had LD 50 values similar to the parental strain; however, the DsctU Bp3 mutant was significantly attenuated with a log LD 50 of 3.3802 cfu.…”
Section: Ttss3 Is a Virulence Determinant In Hamsterssupporting
confidence: 85%
“…Due to the low number of bacteria in infected tissues, abscess material and excreted pus, cultivation on solid or in liquid media is often negative, particularly if samples originate from subclinical or chronic cases (Bongert 1927;Miller et al 1948;Arun et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Little work has been undertaken in non-human primates (NHP). In the 1940's, six Macaca mulatta were challenged subcutaneously with B. mallei, with all animals surviving the challenge and one animal exhibited a raised fever with an abscess at the site of inoculation (Miller et al 1948). Studies reported in the 1990's have involved both subcutaneous and intravenous B. mallei challenge in NHP's, specifically baboons, but details of the disease presentation are sparse (Manzeniuk et al 1996;Khomiakov et al 1998;Mukhopadhyay et al 2004).…”
Section: Abstract Animal Model Burkholderia Histologymentioning
confidence: 99%
“…Studies reported in the 1990's have involved both subcutaneous and intravenous B. mallei challenge in NHP's, specifically baboons, but details of the disease presentation are sparse (Manzeniuk et al 1996;Khomiakov et al 1998;Mukhopadhyay et al 2004). Early studies investigating experimental melioidosis in NHPs were performed in the 1920's and 1940's where macaques were infected by either the oral or subcutaneous route (Stanton & Fletcher 1925;Miller et al 1948). All animals survived the challenge with minimal, if any, clinical observations.…”
Section: Abstract Animal Model Burkholderia Histologymentioning
confidence: 99%